2016
DOI: 10.3390/healthcare4010003
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Sites: Lessons on Leadership from the Implementation of a Long-term Care Delivery Model (CDM) in Western Canada

Abstract: Residential, long-term care serves vulnerable older adults in a facility-based environment. A new care delivery model (CDM) designed to promote more equitable care for residents was implemented in a health region in Western Canada. Leaders and managers faced challenges in implementing this model alongside other concurrent changes. This paper explores the question: How did leadership style influence team functioning with the implementation of the CDM? Qualitative data from interviews with leadership personnel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Team coaching consequently is a holistic approach for creating meaningful and lasting change for individual team members, the team as a whole, and the organization that the team serves [25]. Coaching is a means of enabling individuals or teams to clarify, prioritize and act towards improving performance through reflection and dialogue [27][28][29][30]. The role of the coach is to provide a unified team's agenda and moderates conversations that foster teamwork towards a shared goal [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Team coaching consequently is a holistic approach for creating meaningful and lasting change for individual team members, the team as a whole, and the organization that the team serves [25]. Coaching is a means of enabling individuals or teams to clarify, prioritize and act towards improving performance through reflection and dialogue [27][28][29][30]. The role of the coach is to provide a unified team's agenda and moderates conversations that foster teamwork towards a shared goal [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies showed that team-related factors could influence leadership: turnover and absence (Cloutier et al , 2016; Havig et al , 2011); interpersonal relations (Corazzini et al , 2015; Havig and Hollister, 2018); workload (Corazzini et al , 2015; Westerberg and Tafvelin, 2014); willingness to be coached (Cummings et al , 2014; Havig et al , 2011); employee well-being and satisfaction (Cummings et al , 2014; Nielsen et al , 2008); self-efficacy (Nielsen et al , 2009; Nielsen and Munir, 2009); and interdependent workgroups (Havig and Hollister, 2018). …”
Section: Resultsmentioning
confidence: 99%
“…Two articles relate a high turnover and/or absence rate of employees to less effective leadership (Cloutier et al , 2016; Havig et al , 2011). In a Western Canadian case study, Cloutier et al (2016) report that “With greater staff mobility and change, the leadership had less knowledge of their staff to mobilize existing skill sets, use the expertise and build cohesion” (Cloutier et al , 2016, p. 12). Close interpersonal relations – staff/staff, leader/staff and staff/resident – were found to be positively related to leadership (Corazzini et al , 2015; Havig and Hollister, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This can make it challenging, if not impossible, to implement and sustain improvement initiatives if home leadership does not protect the time and space required for staff to receive proper education, training, and support (Cammer et al, 2013). For these reasons, organizational support is absolutely essential to implementation of any new practice (Cloutier et al, 2016). As noted by others (Tyler et al, 2014;Rodriguez et al, 2015), good team communication is needed to support unit level changes like CHOICE+.…”
Section: Discussionmentioning
confidence: 99%